2012
DOI: 10.1007/s10896-012-9474-9
|View full text |Cite
|
Sign up to set email alerts
|

Developmental Impacts of Child Abuse and Neglect Related to Adult Mental Health, Substance Use, and Physical Health

Abstract: This study examined the association between officially recorded child abuse and neglect and adult mental health, substance use, and physical health outcomes. Data are from a longitudinal study of more than 30 years in which individuals were interviewed most recently in their mid -30s. Analyses consisted of group comparisons using chi-square tests for categorical variables and independent samples t-tests for continuous measures. Logistic and linear regressions controlled for gender and childhood SES, adult age,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
133
2
6

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 188 publications
(149 citation statements)
references
References 35 publications
8
133
2
6
Order By: Relevance
“…Le risque jusqu'à 5,5 fois plus élevé de consulter un médecin et d'être hospitalisé pour des problèmes de santé mentale dans la présente étude concorde avec les résultats d'études antérieures utilisant un devis similaire, mais effectuées auprès d'adultes (Herrenkohl, Hong, Klika, Herrenkohl et Russo, 2013 ;Herrenkohl, Klika, Herrenkohl, Russo et Dee, 2012). Par exemple, après avoir contrôlé l'effet d'un certain nombre de variables confondantes (p.…”
Section: Discussionunclassified
See 2 more Smart Citations
“…Le risque jusqu'à 5,5 fois plus élevé de consulter un médecin et d'être hospitalisé pour des problèmes de santé mentale dans la présente étude concorde avec les résultats d'études antérieures utilisant un devis similaire, mais effectuées auprès d'adultes (Herrenkohl, Hong, Klika, Herrenkohl et Russo, 2013 ;Herrenkohl, Klika, Herrenkohl, Russo et Dee, 2012). Par exemple, après avoir contrôlé l'effet d'un certain nombre de variables confondantes (p.…”
Section: Discussionunclassified
“…Par exemple, après avoir contrôlé l'effet d'un certain nombre de variables confondantes (p. ex., âge, état civil, niveau de scolarité), les adultes maltraités durant l'enfance, incluant l'agression sexuelle, étaient jusqu'à 2,88 et 2,44 fois plus à risque d'être atteints de dépression et d'anxiété modérée à sévère, respectivement, et 3,32 fois plus à risque d'abuser de substances en comparaison des adultes de la population générale (Herrenkohl et al, 2013).…”
Section: Discussionunclassified
See 1 more Smart Citation
“…depression, substance abuse, and high-risk sexual behaviors) among the victims; perpetration of violence by themselves; and even death in extreme cases 2,6,7 .…”
Section: Consequences Of the Child Abusementioning
confidence: 99%
“…Indeed, while controlling for gender and childhood SES, Herrenkohl, Seunghye, Klika, Herrenkohl, and Russo (2013) found that adult survivors of childhood maltreatment were more likely to be depressed, anxious, and suffer more mental and physical health problems. Thus, it is apparent that the effects of childhood maltreatment can span a wide range of impairments in adulthood.…”
Section: Introductionmentioning
confidence: 99%